THE ISSUES OF THE NATIONAL LIBERATION UPRISING LED BY KENESARY KASYMOV IN THE WRITINGS OF ILYAS ZHANSUGUROV (Journal of history, 2025)
Ilyas Zhansugurov is widely recognised in Kazakh society as a poet, literary scholar, and journalist. However, many of his works written in the historical genre have remained largely overlooked by the broader reading public. This is due, firstly, to the fact that the poet fell victim to Stalinist repressions and was unjustly persecuted, and secondly, to the strict Soviet censorship policies that led to the prohibition of many of his writings. The aim of this research article is to provide a scholarly analysis of the historical figure of Kenesary Kasymuly and the national liberation movement he led, based on Ilyas Zhansugurov’s historical work «Zhetisu ólkesin orys aluy» (The Russian Conquest of the Zhetysu Region). Particular attention is given to events related to Kenesary’s arrival in the Zhetysu region with his forces, their military operations, and key moments leading up to the final stages of his life.The article employs methods of systematization, analysis, and work with historical facts within a methodological framework grounded in the principles of problem-based inquiry, historicism, and objectivity, as recognized in the field of historical science. These approaches are essential, as it is through the lens of historical fact that the cognitive potential of history as a discipline can be fully realized. Furthermore, the study makes extensive use of oral historical narration and logical generalization methods; given that Ilyas Zhansugurov’s poetic and journalistic talent was deeply rooted in the finest traditions of Kazakh oral folklore. Of particular note is the continuity observed with such works as Nysanbay Zhyrau’s epic «Kenesary – Nauryzbay», as well as with the broader oral historical tradition.The scholarly novelty of our research lies in the identification of Ilyas Zhansugurov’s comprehensive examination of the Russian Empire’s colonial policy. The national liberation uprising led by Kenesary Kasymuly an all-national response to violent colonization is also deeply reflected in Zhansugurov’s body of work. Special emphasis is placed on the final and decisive stage of the rebellion, namely the actions carried out in the Zhetysu region, which are analyzed not only from a historical perspective but also through the lens of artistic perception, as conveyed in his poem «Kuyshi». This dual approach enables a more profound understanding of the internal dynamics and distinctive characteristics of the uprising. Additionally, the study concludes that the poet was well acquainted with the works of Nysanbay zhyrau and the subsequent generations of akyns and zhyraus, drawing spiritual inspiration and ideological continuity from their creative legacy.In the course of examining the colonization of the Zhetysu region by the Russian Empire and the final stage of the uprising led by Kenesary Kasymuly, we arrive at a well-founded conclusion regarding the necessity of giving due attention to the works of Ilyas Zhansugurov. His historical writings provide a deeper and more comprehensive understanding of the issues at hand. Therefore, it seems appropriate that the works of the poet mentioned in the article should be subject to the attention of professional historians and incorporated into their scholarly research.
Keywords: Zhetisu, Russian, Kokand, Uly zhuz, uprising, sultan, manap.